2013
DOI: 10.4049/jimmunol.1203279
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex B Cell Characterization in Blood, Lymph Nodes, and Tumors from Patients with Malignancies

Abstract: B lymphocytes contribute to immune surveillance, by tumor-specific Abs and Ag presentation to T lymphocytes, but are insufficiently studied in humans. In this article, we report a flow cytometric investigation of B lymphocyte subpopulations in blood, lymph nodes (LNs), and malignant tissues from 20 patients operated on because of advanced solid tumors. The CD19+ compartment in peripheral blood was essentially unaltered in patients, as compared with healthy control subjects. In metastatic LNs, signs of B lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 41 publications
(58 reference statements)
7
41
0
Order By: Relevance
“…In addition, experimental studies revealed that B cells can both positively and negatively regulate T cell mediated antitumor immune response, by acting as antigen presenting cells or via chemokine secretion. [36][37][38][39] Altogether our data shed light on a subcapsular B cell rich microenvironment whose function in generating a specific pre-metastatic niche for metastase hosting remains to be determined. Of utmost interest, we establish for the first time a link between lymphatic vessels, CD20…”
mentioning
confidence: 84%
“…In addition, experimental studies revealed that B cells can both positively and negatively regulate T cell mediated antitumor immune response, by acting as antigen presenting cells or via chemokine secretion. [36][37][38][39] Altogether our data shed light on a subcapsular B cell rich microenvironment whose function in generating a specific pre-metastatic niche for metastase hosting remains to be determined. Of utmost interest, we establish for the first time a link between lymphatic vessels, CD20…”
mentioning
confidence: 84%
“…These effects may at least be partly target specific. Analysis of B cells from tumors and metastatic lymph nodes found hypermutated antibody genes and expansion of class-switched memory cells and plasmablasts in patients with bladder cancer [17]. Intratumoral germinal centers (GCs) have been reported to be present in NSCLC [18][19][20], breast cancer [21][22][23][24], colon cancer [25], and germ cell cancers [26].…”
mentioning
confidence: 99%
“…Our studies, initially focused on CD4 + T cells infiltrating breast tumors, were quickly presented with a major technical problem due to cleavage of surface CD4 receptors using standard enzymatic digestion protocols [4][5][6][7][8] . We tested a variety of collagenase enzymes with or without DNase and hyaluronidase inhibitors, finding that collagenase I and II completely removed CD4 from the cell surface, despite high lymphocyte viability ( Figure 3A).…”
Section: Representative Resultsmentioning
confidence: 99%
“…Dissociating tumor tissue while maintaining cellular integrity is technically challenging and has traditionally been performed using a combination of mechanical and enzymatic steps to prepare single cell suspensions [4][5][6][7][8] . This approach involves lengthy incubation periods and is associated with a significant reduction in cell viability as well as the loss of cell surface receptors by enzymatic cleavage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation